2006
DOI: 10.1196/annals.1372.038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Exocrine Pancreatic Insufficiency in Streptozotocin‐Induced Type 1 Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is a major health problem at present affecting about 180 million people worldwide. DM is associated with many metabolic abnormalities in the body including the indigestion of carbohydrates leading to malnutrition and weight loss. In this article we investigate the cellular and molecular mechanisms of exocrine pancreatic insufficiency in streptozotocin (STZ, 60 mg kg(-1), i.p.)-induced DM in male rats compared to healthy age-matched controls. Either electrical field stimulation (EFS) or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 40 publications
3
23
1
Order By: Relevance
“…Streptozotocin is a chemical agent used to produce type 1 diabetes in animal model due to selective destruction of β-islet cells of the pancreas which leads to impaired insulin secretion [20]. In our study, 3 weeks after single injection of streptozotocin, rats showed hypoinsulinemia and hyperglycemia, as expected.…”
Section: Discussionsupporting
confidence: 56%
“…Streptozotocin is a chemical agent used to produce type 1 diabetes in animal model due to selective destruction of β-islet cells of the pancreas which leads to impaired insulin secretion [20]. In our study, 3 weeks after single injection of streptozotocin, rats showed hypoinsulinemia and hyperglycemia, as expected.…”
Section: Discussionsupporting
confidence: 56%
“…A reduced secretion capacity of exocrine pancreas has been reported in diabetic humans [27] and adult rats with streptozotocin-induced diabetes [28] , but from the present results it is not possible to assess whether the rats subjected to fetal undernutrition in our study would have developed diabetes as they grew older, possibly secondary due to pancreatic dysfunction, though this is an intriguing possibility. This should be investigated further in a study where the experimental animals would be followed to an older age.…”
Section: Discussioncontrasting
confidence: 52%
“…As a result of STZ action, pancreatic ␤-cells are destroyed by necrosis (Mythili et al, 2004). In adult rats, 60 mg/kg is the most common dose of STZ to induce insulin dependent diabetes (Patel et al, 2006), but higher doses are also used. STZ is also efficacious after intraperitoneal administration of a similar or higher dose, but single doses below 40 mg/kg may be ineffective (Katsumata et al, 1992).…”
Section: Inhibitors Alpha-glucosidase Inhibitorsmentioning
confidence: 99%